Hydrodesulfurization of Dibenzothiophene: A Machine Learning Approach - Dr. Guadalupe Castro; Dr. Julián Cruz‐Borbolla; Dr. Marcelo Galván; Dr. Alfredo Guevara‐García; Dr. Joel Ireta; Dr. Myrna H. Matus; Dr. Amilcar Meneses‐Viveros; Dr. Luis Ignacio Perea‐Ramírez; Miriam Pescador‐Rojas (ChemistryOpen, 2024)
Abstract The hydrodesulfurization (HDS) process is widely used in the industry to eliminate sulfur compounds from fuels. However, removing dibenzothiophene (DBT) and its derivatives is a challenge. Here, the key aspects that affect the efficiency of catalysts in the HDS of DBT were investigated using machine learning (ML) algorithms. The conversion of DBT and selectivity was estimated by applying Lasso, Ridge, and Random Forest regression techniques. For the estimation of conversion of DBT, Random Forest and Lasso offer adequate predictions. At the same time, regularized regressions have similar outcomes, which are suitable for selectivity estimations. According to the regression coefficient, the structural parameters are essential predictors for selectivity, highlighting the pore size, and slab length. These properties can connect with aspects like the availability of active sites. The insights gained through ML techniques about the HDS catalysts agree with the interpretations of previous experimental reports.